The European Pilgrimage Routes for promoting sustainable and quality tourism in rural areas International Conference proceedings 4-6 December 2014, Firenze - Italy - BAMBI, FEDERIGO; Barbari, Matteo (Proceedings e report, 2015)
The International Conference the European Pilgrimage Routes for promoting sustainable and quality tourism in rural areas took place December 4 to 6, 2014 in Firenze (Italy) and was organized by the Department of Agricultural, Food and Forestry Systems - University of Florence in collaboration with the Tuscany Region, the Department for Life Quality Studies and Department of Agricultural Sciences - University of Bologna, the Italian Association of Agricultural Engineering and the European Association of the Francigena Way. The Conference involving 150 experts from 18 countries and was divided into five areas of discussion: conservation and evolution of the landscape along the routes; life quality and social impact; tourism and local development; sustainability in the rural areas; tools and methods for building a tourist attraction.